The Lord of Mantralaya : [a life sketch of Sri Raghavendra Swamiji of Mantralaya] - Acharya, J. H. B. (for copies, J. H. Sumithra Bai], 1974)
On the life of the Vaishnavite religious leader Swami Raghavendra, 1601-1661, of the Madhva school of the Dvaita Vedanta philosophy; a study.